Mammalian‐target of rapamycin inhibition with temsirolimus in myelodysplastic syndromes (MDS) patients is associated with considerable toxicity: results of the temsirolimus pilot trial by the German MDS Study Group (D‐MDS). (7th October 2016) - Wermke, Martin; Schuster, Claudia; Nolte, Florian; Al‐Ali, Haifa‐Kathrin; Kiewe, Philipp; Schönefeldt, Claudia; Jakob, Christiane; von Bonin, Malte; Hentschel, Leopold; Klut, Ina‐Maria; Ehninger, Gerhard; Bornhäuser, Martin; et al.
Summary: The mammalian‐target of rapamycin (also termed mechanistic target of rapamycin, mTOR) pathway integrates various pro‐proliferative and anti‐apoptotic stimuli and is involved in regulatory T‐cell (TREG) development. As these processes contribute to the pathogenesis of myelodysplastic syndromes (MDS), we hypothesized that mTOR modulation with temsirolimus (TEM) might show activity in MDS. This prospective multicentre trial enrolled lower and higher risk MDS patients, provided that they were transfusion‐dependent/neutropenic or relapsed/refractory to 5‐azacitidine, respectively. All patients received TEM at a weekly dose of 25 mg. Of the 9 lower‐ and 11 higher‐risk patients included, only 4 (20%) reached the response assessment after 4 months of treatment and showed stable disease without haematological improvement. The remaining patients discontinued TEM prematurely due to adverse events. Median overall survival (OS) was not reached in the lower‐risk group and 296 days in the higher‐risk group. We observed a significant decline of bone marrow (BM) vascularisation ( P = 0·006) but were unable to demonstrate a significant impact of TEM on the balance between TREG and pro‐inflammatory T‐helper‐cell subsets within the peripheral blood or BM. We conclude that mTOR‐modulation with TEM at a dose of 25 mg per week is accompanied by considerable toxicity and has no beneficial effects in elderly MDS patients.